Peer review of the pesticide risk assessment of the active substance flutolanil - European Food Safety Authority (EFSA); Fernando Alvarez; Maria Arena; Domenica Auteri; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; Isabella De Magistris; et al. (EFSA Journal)
Abstract The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, the Netherlands, and co‐rapporteur Member State, the United Kingdom, for the pesticide active substance flutolanil, and the assessment of applications for maximum residue levels (MRLs) are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of flutolanil as a fungicide on potatoes, tulips and iris (field uses). MRLs were assessed for a potato in‐furrow treatment. The reliable end points, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.